Removal of phosphate from wastewater using zirconium/iron embedded chitosan/alginate hydrogel beads: An experimental and computational perspective - Ahmed, Aminat Mohammed; Mekonnen, Menbere Leul; Jote, Bikila Alemu; Damte, Jemal Yimer; Mengesha, Ephriem Tadesse; Lednický, Tomáš; Mekonnen, Kebede Nigussie (International journal of biological macromolecules, 2024)
Adsorptive removal of phosphate plays a crucial role in mitigating eutrophication. Herein, the Zr/Fe embedded chitosan/alginate hydrogel bead (Zr/Fe/CS/Alg) is reported as an effective phosphate adsorbent. This polymer nanocomposite is synthesized by the in-situ reduction of the metals on the polymer matrix. The synthesized adsorbent was characterized by the FTIR, SEM-EDX, TGA, BET, and XPS. The adsorbent showed a maximum phosphate adsorption capacity of 221.72 mg/g at pH 3. The experimental data fit well with the Freundlich isotherm and pseudo-second-order kinetics model, indicating a heterogeneous multilayer surface formation and a chemisorption-dominated adsorption process. Density Functional Theory (DFT) and Monte Carlo (MC) calculations revealed high negative adsorption energy due to the chemisorption of phosphate on the adsorbent. Hence, the major interactions such as electrostatic attraction, hydrogen bonding, and inner-sphere complexation of phosphate adsorption and Zr/Fe/CS/Alg hydrogel beads were investigated from the experimental and computational analysis. The negative values of thermodynamic parameters indicated a spontaneous, exothermic, and less random adsorption process. The synthesized adsorbent exhibited excellent selectivity toward phosphate and maintained 73 % efficiency after six adsorption/desorption cycles. The Zr/Fe/CS/Alg hydrogel beads reduced the phosphate concentration in real wastewater samples from 19.02 mg/L to 0.985 mg/L, suggesting that these nanocomposite hydrogel beads could be a promising adsorbent for real-world applications.
Keywords: kinetika; Chitosan; Thermodynamics; Alginates; odpadní voda; Zirconium; Fe-Zr-polymer nanocomposite; koncentrace vodíkových iontů; čištění vody; fosfáty; Hydrogels; Phosphates; Wastewater; algináty; Water Pollutants, Chemical; Adsorption; chemické látky znečišťující vodu; Alginate; termodynamika; Iron; chitosan; Water Purification; adsorpce; zirkonium; Hydrogen-Ion Concentration; hydrogely; železo; Kinetics; Phosphate removal